Key factors for successful implementation of a participatory ergonomics program - Jatczak, Mark (My University, 2009)
Inadequate workplace ergonomics can lead to injuries, productivity declines and quality issues. Despite the fact that ergonomics has been researched and implemented in the workplace for the past 20-30 years work-related musculoskeletal disorders (WMSDs) remain as the most expensive category of injuries. It has not been widely understood why some ergonomic interventions are effective at some workplaces while not effective in others. However, one approach can be used to reduce musculoskeletal injuries is participative or participatory ergonomics. Participative ergonomics evolved out of Quality Circles utilized in Japanese manufacturing plants in the 1960s. Participatory ergonomics is defined as the process by which management and labor work together to modify and/or design the work space, task, equipment and environment to better fit an individual?s abilities and limitations. A lack of impact is not unusual in cooperative situations involving labor and management. It is quite common for such teams to underachieve and is the point of emphasis of this research study. Inconsistent results indicate the need to better understand the dynamics involved with such a team in order to determine key elements for success. It was the intent of this research to analyze successful ergonomics teams via a survey approach to better understand these key factors. After identifying high-performing participatory ergonomics teams within the manufacturing sector (SIC 20-39), a survey was distributed to thirty-five facilities in the Midwest and California. Twenty-five of these surveys were completed and returned to the researcher. Of the 25 respondents (48%) reported that their participatory ergonomics program had been in place for 10 years or more, 6 (24%) had programs in place for 5-10 years, 6 (24%) had programs for 2-5 years and only 1 respondent (4%) had a program in place for 1-2 years. The data collected showed that an organization?s culture and ergonomic process were two areas indicated to be important to a team?s success. Specifically, creating a culture of teamwork and committing to a participative work style were two of the most highly scored items. Other significant findings of this research indicated that the organizations that participated focused on several key areas in order to create and sustain a participatory ergonomics team: create a culture of teamwork, commit to a participative working style, ask affected employees for their input and use formal evaluation tools for assessing ergonomic hazards.
Date original created: Nov. 5, 2008. This file was last viewed in Adobe Reader 8.0
Keywords: Human engineering; Teams in the workplace; Industrial hygiene